Business angels and Agency Costs - GUERIN, Nicolas (2016)
This paper examines business angels’ behaviours towards agency costs by studying how business angels reduce conflicts of interests with entrepreneurs. The theoretical framework of this paper is based on the agency theory and the incomplete contract theory. In order to make this study more accurate, corporate governance mechanisms were also used to decipher and understand business angels’ behaviours. Using these theories, the research framework is based on four different areas of interest: contracts and the different rights these involve, informal and formal involvement of business angels in investments, the relationship between the entrepreneurs and the business angels and finally corporate governance mechanisms.